Role of Platinum Nanozymes in the Oxidative Stress Response of Salmonella Typhimurium - Mireya Viviana Belloso Daza; Anna Scarsi; Francesca Gatto; Gabriele Rocchetti; Pier Paolo Pompa; Pier Sandro Cocconcelli (MDPI AG, 2023)
Platinum nanoparticles (PtNPs) are being intensively explored as efficient nanozymes due to their biocompatibility coupled with excellent catalytic activities, which make them potential candidates as antimicrobial agents. Their antibacterial efficacy and the precise mechanism of action are, however, still unclear. In this framework, we investigated the oxidative stress response of Salmonella enterica serovar Typhimurium cells when exposed to 5 nm citrate coated PtNPs. Notably, by performing a systematic investigation that combines the use of a knock-out mutant strain 12023 HpxF- with impaired response to ROS (ΔkatE ΔkatG ΔkatN ΔahpCF ΔtsaA) and its respective wild-type strain, growth experiments in both aerobic and anaerobic conditions, and untargeted metabolomic profiling, we were able to disclose the involved antibacterial mechanisms. Interestingly, PtNPs exerted their biocidal effect mainly through their oxidase-like properties, though with limited antibacterial activity on the wild-type strain at high particle concentrations and significantly stronger action on the mutant strain, especially in aerobic conditions. The untargeted metabolomic analyses of oxidative stress markers revealed that 12023 HpxF- was not able to cope with PtNPs-based oxidative stress as efficiently as the parental strain. The observed oxidase-induced effects comprise bacterial membrane damage as well as lipid, glutathione and DNA oxidation. On the other hand, in the presence of exogenous bactericidal agents such as hydrogen peroxide, PtNPs display a protective ROS scavenging action, due to their efficient peroxidase mimicking activity. This mechanistic study can contribute to clarifying the mechanisms of PtNPs and their potential applications as antimicrobial agents.